Urgency of Chemistry Instrumentation for Students of Medical Laboratory Technology - endang tri wahyuni maharani; yusrin Yusrin (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2019)
The background of the research is that the chemical instrumentation course reviews all instrumentation used for health laboratory examinations in accordance with the demands of a health analyst's competence. This material is basic knowledge, so students need to understand these three aspects, namely: the concept and function of chemical instrumentation, the basics of chemical instrumentation analysis, and the classification of chemical analysis.The research method is quantitative descriptive with 80 students and the main data collection tool is a questionnaire / instrument. Variables were examined from all three aspects, each aspect contain 20 questions, so that in the whole questionnaire there were 60 questions. efore the questionnaire was used to retrieve data, the validity and reliability tests had been carried out and the results were declared valid and reliable, while the data analysis technique was used descriptive analysis by comparing the calculated results with the criteria set by the researcher.The results of the study concluded: 1) the concept and function of chemical instrumentation obtained a score of 69 or 86.25% with very good criteria; 2) the basics of chemical instrumentation analysis obtained a score of 72 or 90.00% with good criteria; and 3) the classification of chemical analysis obtained a score of 73 or 91.25% with very good criteria, so the final conclusion is the perception of Health Analyst students' study programs on the urgency of chemical instrumentation material is very good.